Implementasi Akad Pembiayaan Murabahah Pada BMT UGT Sidogiri Cabang Jember - Zainuddin Zainuddin (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2021)
The majority of the financing portfolio in Syari'ah Financial Institution was dominated by murabahah financing. In this study, the researcher had examined the implementation of akad in murabahah financing at BMT UGT Sidogiri branch Jember. This study used the descriptive qualitative method. From the results, it can be concluded that, first, the implementation of Murabahah financing at BMT Sidogiri branch Jember was engaged in the micro-economic, and it was a halal business. Second, the mechanism of murabahah financing at BMT Sidogiri in Jember Branch was broadly in line with the rules of the principles of shari'ah economy. But the procurement of goods still using akad wakalah.